I'm learning the basics of proof by induction and wanted to see if I took the right steps with the following proof:
Theorem: for n∈N,n∑k=1(2k+1)=n2+2n
Base Case:
let n=1
Therefore 2∗1+1=12+2∗1
Which proves base case is true.
Inductive Hypothesis:
Assume n∑k=1(2k+1)=n2+2n
Then n+1∑k=1(2k+1)=(n+1)2+2(n+1)
⟺(2(n+1)+1)+n∑k=1(2k+1)=(n+1)2+2(n+1)
Using inductive hypothesis on summation term:
⟺(2(n+1)+1)+n2+2n=(n+1)2+2(n+1)
⟺2(n+1)=2(n+1)
Hence for n∈N,n∑k=1(2k+1)=n2+2n Q.E.D.
Does this prove the theorem? Or was my use of the inductive hypothesis circular logic?
Answer
Your proof looks fine, but if you know that
1+2+...+n=n(n+1)2
then you can evaluate
n∑k=1(2k+1)=2n∑k=1k+n∑k=11=/2n(n+1)/2+n=n2+2n
No comments:
Post a Comment